Significance of Indoleamine 2,3-Dioxygenase Expression in the Immunological Response of Kidney Graft Recipients - Krzysztof Wiśnicki; Piotr Donizy; Agata Remiorz; Dariusz Janczak; Magdalena Krajewska; Mirosław Banasik (Diagnostics, 2022)
Kidney transplantation is unquestionably the most advantageous and preferred treatment when patients with end-stage renal disease are considered. It does have a substantially positive influence on both the quality and expectancy of their lives. Thus, it is quintessential to extend the survival rate of kidney grafts. On account of T-cell-focused treatment, this is being exponentially achieved. The kynurenine pathway, as an immunosuppressive apparatus, and indoleamine 2,3-dioxygenase (IDO1), as its main regulator, are yet to be exhaustively explored. This review presents the recognised role of IDO1 and its influence on the kynurenine pathway, with emphasis on immunosuppression in kidney transplant protection.